PENGARUH PROFESIONALISME, MACHIAVELLIANISME, DAN LINGKUNGAN ETIKA TERHADAP WHISTLEBLOWING DENGAN MODERASI LOCUS OF CONTROL - Alvionita, Nanda; Aufa, Muhammad (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2023)
Academic fraud is categorized as an act of deception in the campus environment and is an important topic to study. Academic fraud includes copying friends' answers, manipulating attendance, asking others to do assignments, falsifying diplomas and others. With Whistleblowing having a very important role in minimizing fraudulent practices, the purpose of this study is to examine the effect of professional commitment, ethical environment and Machiavellian attitudes on whistleblowing intentions with accounting students at all universities in Gresik. This study uses a quantitative approach as a research method with non-probability sampling. With a total of 625 responses, the sample size was calculated using the Slovin formula at a 5% significance level. The professional commitment variable has no effect on whistleblowing intentions. Likewise, the locus of control variable also cannot moderate between professional commitment and whistleblowing intentions. However, the machiavellian attitude and ethical environment variables have an influence on whistleblowing intentions. Meanwhile, locus of control is accepted as a moderating variable between Machiavellian attitudes and the ethical environment.